Hot Upper Mantle Beneath the Tristan da Cunha Hotspot From Probabilistic Rayleigh‐Wave Inversion and Petrological Modeling. (8th May 2018) - Bonadio, Raffaele; Geissler, Wolfram H.; Lebedev, Sergei; Fullea, Javier; Ravenna, Matteo; Celli, Nicolas L.; Jokat, Wilfried; Jegen, Marion; Sens‐Schönfelder, Christoph; Baba, Kiyoshi
Abstract: Understanding the enigmatic intraplate volcanism in the Tristan da Cunha region requires knowledge of the temperature of the lithosphere and asthenosphere beneath it. We measured phase‐velocity curves of Rayleigh waves using cross‐correlation of teleseismic seismograms from an array of ocean‐bottom seismometers around Tristan, constrained a region‐average, shear‐velocity structure, and inferred the temperature of the lithosphere and asthenosphere beneath the hotspot. The ocean‐bottom data set presented some challenges, which required data‐processing and measurement approaches different from those tuned for land‐based arrays of stations. Having derived a robust, phase‐velocity curve for the Tristan area, we inverted it for a shear wave velocity profile using a probabilistic (Markov chain Monte Carlo) approach. The model shows a pronounced low‐velocity anomaly from 70 to at least 120 km depth. V S in the low velocity zone is 4.1–4.2 km/s, not as low as reported for Hawaii (∼4.0 km/s), which probably indicates a less pronounced thermal anomaly and, possibly, less partial melting. Petrological modeling shows that the seismic and bathymetry data are consistent with a moderately hot mantle (mantle potential temperature of 1, 410–1, 430°C, an excess of about 50–120°C compared to the global average) and a melt fraction smaller than 1%. Both purely seismic inversions and petrological modeling indicate a lithospheric thickness of 65–70 km, consistent with recent estimates from receiver functions. The presence of warmer‐than‐average asthenosphere beneath Tristan is consistent with a hot upwelling (plume) from the deep mantle. However, the excess temperature we determine is smaller than that reported for some other major hotspots, in particular Hawaii. Plain Language Summary: The chains of volcanic ocean islands such as Hawaii are created when oceanic tectonic plates move over anomalously hot regions (hotspots) in the underlying mantle. The origin of hotspots has been attributed to mantle plumes, spectacular hot upwellings from the Earth's core‐mantle boundary (2, 800 km depth). The existence of the plumes and their occurrence beneath particular locations of volcanism are a matter of a heated debate. One way to find out whether a hot upwelling may be present is to determine the temperature in the mantle at depths just beneath the tectonic plate in the location of a hotspot. These depths are around 100 km, however, and temperature there cannot be measured directly. In this study, we used new seismic data from an array of ocean‐bottom seismometers deployed around Tristan da Cunha, a prominent hotspot in the South Atlantic Ocean, and determined seismic velocities beneath it. Seismic velocities depend on the temperature of the mantle rock. We were able to use this dependence to infer the temperature within and below the tectonic plate around Tristan. The temperature is anomalously high. This is consistent with a hot mantle plume reaching Tristan from below and causing the unusual, long‐lived volcanism at this location. Key Points: Lithosphere beneath Tristan is 65–70 km thick; the low‐velocity zone below shows V S of 4.1–4.2 km/s Mantle potential temperature that fits surface wave and other data is 1, 410–1, 430°C The high mantle temperature is consistent with a plume origin of volcanism, but it is lower than beneath Hawaii